Prognostic Implications of Left Ventricular Dyssynchrony for Major Adverse Cardiovascular Events in Asymptomatic Women and Men: The Multi‐Ethnic Study of Atherosclerosis. Issue 4 (1st August 2014) - Sharma, Ravi K.; Volpe, Gustavo; Rosen, Boaz D.; Ambale‐Venkatesh, Bharat; Donekal, Sirisha; Fernandes, Veronica; Wu, Colin O.; Carr, Jeffrey; Bluemke, David A.; Lima, João A. C.
Abstract : Background: Left ventricular (LV) dyssynchrony is related to adverse outcomes in systolic heart failure, but its prognostic importance in asymptomatic population is not known. Our objective was to assess the prognostic implications of LV mechanical dyssynchrony in a large multiethnic population before the occurrence of global LV dysfunction. Methods and Results: A total of 1392 participants in the Multi‐Ethnic Study of Atherosclerosis (MESA; mean age: 64.7 years; 46% were women) with cardiac magnetic resonance imaging at baseline were followed for a median duration of 8.3 years. Harmonic phase imaging analysis was used to derive systolic circumferential strain. Greater standard deviation of time to peak systolic strain (SD‐TPS) indicates greater dyssynchrony. With SD‐TPS as a continuous variable, Cox proportional hazards analysis was used to assess hazards ratio after adjusting for demographics, cardiovascular risk factors, LV mass‐to‐volume ratio, and ejection fraction. Using the 75th percentile of SD‐TPS as a cutoff, Kaplan–Meier analysis was performed between 2 categorical groups for each gender. Higher values of dyssynchrony in women predicted major adverse cardiovascular events, defined as myocardial infarction, heart failure, stroke, and death (hazard ratio: 1.01 per 1‐ms increment in SD‐TPS, P =0.015), hard coronary events (hazard ratio: 1.05 per 1‐ms increment in SD‐TPS, P =0.026), and cerebrovascular events (hazard ratio: 1.03 per 1‐ms increment in SD‐TPS, P =0.013). In contrast, dyssynchrony in men was not predictive of events. Kaplan–Meier analyses in women revealed increased event occurrence in the higher dyssynchrony group, but this was not the case in men. Conclusions: In an asymptomatic cohort, greater LV dyssynchrony determined by cardiac magnetic resonance imaging predicts adverse cardiovascular outcome in women but not in men. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT00005487.